Pulmonary hypertension among children with in-hospital cardiac arrest: A multicenter study. (November 2021) - Morgan, Ryan W.; Himebauch, Adam S.; Griffis, Heather; Quarshie, William O.; Yeung, Timothy; Kilbaugh, Todd J.; Topjian, Alexis A.; Traynor, Danielle; Nadkarni, Vinay M.; Berg, Robert A.; Nishisaki, Akira; Sutton, Robert M.
Abstract: Aims: To determine the prevalence of pulmonary hypertension (PH) among children with in-hospital cardiac arrest (IHCA) and its association with survival. Methods: Children (<18 years) admitted to ICUs participating in the Virtual Pediatric Systems multicenter registry between January 2011 and December 2017 who had an IHCA during their hospitalization were included. Patients were classified by whether they had a documented diagnosis of PH at the time of IHCA. Clinical characteristics were compared between patients with and without PH. After propensity score matching, conditional logistic regression within the matched cohort determined the association between PH and survival to hospital discharge. Results: Of 18, 575 children with IHCA during the study period, 1, 590 (8.6%) had a pre-arrest diagnosis of PH. Patients with PH were more likely to be 29 days to 2 years of age, female, Black/African American, and American Indian/Alaskan Native, and to be treated in a cardiac ICU or mixed PICU/cardiac ICU. At ICU admission, PH patients had a lower probability of death as determined by the Pediatric Index of Mortality 2 (PIM-2) score. Patients with PH were more likely to be receiving inhaled nitric oxide (13.0% vs. 2.1%; p < 0.001). Propensity score matching successfully matched 1, 302 PH patients with 3, 604 non-PH patients. Patients with PH were less likely to survive to hospital discharge (aOR 0.83; 95% CI: 0.72–0.95; p = 0.01) than non-PH patients. Conclusions: In this large multicenter study, 8.6% of children with IHCA had pre-existing documented PH. These children were less likely to survive to hospital discharge than those without PH.